Governance and Development Sharia Micro Wakaf Bank Towards Medium Small Micro Enterprises - Setiyadi, Amin; Noviarita, Heni (Dirham: Journal of Sharia Finance and Economics, 2026)
Purpose: This study examines the governance and distribution of Islamic micro waqf banks to micro, small, and medium enterprises (MSMEs) in Indonesia. Research Methodology: This study used a qualitative approach with secondary data, including a literature review. The literature sources were gathered from journals, books, and relevant Internet sources related to the governance and development of Islamic micro waqf banks. Results: This study concludes that the governance of micro waqf banks includes management functions such as planning, organizing, leadership, and supervision, while ensuring that operations follow Sharia principles. Islamic micro waqf banks are predominantly distributed in Java, with East Java, Central Java, and West Java having the highest concentrations, followed by Yogyakarta and Banten. Conclusions: Islamic micro-waqf banks’ governance is crucial for their operational success, with management practices aligned with Sharia principles. The distribution of these banks is most prominent in Java, contributing to MSME empowerment in the region. Limitations: This research is limited by the availability of relevant literature and in-depth analysis of the topic. The study also highlights that Islamic micro waqf banks are still a relatively new concept, with limited establishment across the country and limited funding. Contributions: The researchers hope that this study provides valuable information and insights for students, academics, managers of Islamic micro waqf banks, and society.